Adenovirus-Vectored African Swine Fever Virus pp220 Induces Robust Antibody, IFN-γ, and CTL Responses in Pigs - Zajac, Michelle D.; Sangewar, Neha; Lokhandwala, Shehnaz; Bray, Jocelyne; Sang, Huldah; McCall, Jayden; Bishop, Richard P.; Waghela, Suryakant D.; Kumar, Rakshith; Kim, Tae; Mwangi, Waithaka (Frontiers in Veterinary Science, 2022)
African Swine Fever Virus (ASFV) poses a serious threat to the pork industry worldwide; however, there is no safe vaccine or treatment available. The development of an efficacious subunit vaccine will require the identification of protective antigens. The ASFV pp220 polyprotein is essential for virus structural integrity. This polyprotein is processed to generate p5, p34, p14, p37, and p150 individual proteins. Immunization of pigs with a cocktail of adenoviruses expressing the proteins induced significant IgG, IFN-γ-secreting cells, and cytotoxic T lymphocyte responses. Four predicted SLA-I binding nonamer peptides, namely p34161−169, p37859−867, p1501363−1371, and p1501463−1471, recalled strong IFN-γ+ PBMC and splenocyte responses. Notably, peptide p34161−169 was recognized by PBMCs isolated from 7/10 pigs and by splenocytes isolated from 8/10 pigs. Peptides p37859−867 and p1501363−1371 stimulated recall IFN-γ+ responses in PBMCs and splenocytes isolated from 8/10 pigs, whereas peptide p1501463−1471 recalled responses in PBMCs and splenocytes isolated from 7/10 to 9/10 pigs, respectively. The results demonstrate that the pp220 polyprotein contains multiple epitopes that induce robust immune responses in pigs. Importantly, these epitopes are 100% conserved among different ASFV genotypes and were predicted to bind multiple SLA-I alleles. The outcomes suggest that pp220 is a promising candidate for inclusion in a prototype subunit vaccine.